EuroGEMS.org: Guide and links to online genetic and genomic educational resources, valuable for all levels. Issue 12 (10th October 2020) - Tobias, Adam P.; Tobias, Edward S.
Abstract: There is a well‐recognized growing need for improved access to online genetic and genomics education for professionals, students, teachers, and the public. Numerous individual online genetic and genomic educational resources have been developed, but many are difficult to identify or locate when required. Consequently, an easily navigated website, European Society of Human Genetics (ESHG) Genetic Educational Materials and Sources (https://www.EuroGEMS.org ), has recently been created, on behalf of the ESHG, by the authors. It facilitates access by a wide variety of target audience types and levels to a broad range of 110 selected, free, high‐quality educational online genetic and genomic resources around the world, including several in languages other than English. The website has been endorsed by the ESHG, directly linked from that society's web pages, and has now been used in over 105 countries. Abstract : This invited Special Article describes http://www.EuroGEMS.org, a valuable web‐based guide with links to 110 carefully selected, free, high‐quality international online genetic and genomic information sources, including sites related to COVID‐19. Created on behalf of the European Society of Human Genetics and already used around the world, EuroGEMS.org contains sections for different target audiences, including genetics and genomics professionals, students, schools, and the public